Feasibility, acceptability and outcomes at a 12-month follow-up of a novel community-based intervention to prevent type 2 diabetes in adults at high risk: mixed methods pilot study. Issue 11 (12th November 2013) - Penn, Linda; Ryan, Vicky; White, Martin
Abstract : Objectives and design: Lifestyle interventions can prevent type 2 diabetes (T2D) in adults with impaired glucose tolerance. In a mixed methods pilot study, we aimed to assess the feasibility, acceptability and outcomes at a 12-month follow-up of a behavioural intervention for adults at risk of T2D. Participants: Adults aged 45–65 years with a Finnish Diabetes Risk Score (FINDRISC) ≥11. Setting: The intervention was delivered in leisure and community settings in a local authority that ranks in the 10 most socioeconomically deprived in England. Intervention: A 10-week supported programme to promote increased physical activity (PA), healthy eating and weight loss was delivered by fitness trainers as twice-weekly group PA or cookery sessions, each followed by behavioural counselling with support to 12 months. Outcome measures: We assessed feasibility and acceptability of the intervention, and change in behavioural and health-related outcomes at 6 and 12 months. Results: From 367 registers of interest, 218 participants were recruited to the programme with baseline mean (SD): age 53.6 (6) years, FINDRISC 13.9 (3.1), body mass index 33.5 (5.9) kg/m 2, waist circumference 108.1 (13.7) cm, PA levels (self-report): daily total 49.1 (5.9) metabolic-equivalent (MET) h/day. Follow-up at 12 months was completed by 134 (61%) participants, with an estimated mean (95% CI) change from baseline in weight −5.7 (−7.8 to −2.8); −2.8 (−3.8 to −1.9) kg, waist circumference −7.2 (−9.2 to −5.2); −6.0 (−7.1 to −5.0) cm, and PA level 7.9 (5.8 to 10.1); 6.7 (5.2 to 8.2) MET h/day equivalent, for men and women, respectively (from covariance pattern mixed models). Participants reported an enjoyable, sociable and supportive intervention experience. Conclusions: Participants' views indicated a high level of intervention acceptability. High retention and positive outcomes at 12 months provide encouraging indications of the feasibility and potential effectiveness of the intervention. A definitive trial of this intervention is warranted.